USE OF VILLAGE FUNDS BASED ON GOVERNMENT REGULATIONS NUMBER 60 OF 2014 - Irwansyah, Irwansyah; Lubis, Muhammad Ansori (Jurnal Ilmiah METADATA, 2025)
Village funds are managed in an orderly manner, in accordance with the provisions of laws and regulations, efficiently, economically, effectively, transparently, and responsibly, with due regard for a sense of justice and propriety, and prioritizing the interests of the local community. Regulations on the use of village funds based on Government Regulation Number 60 of 2014 are used for physical development and community empowerment. Village funds are a very helpful and very effective policy in supporting the implementation of village government programs. The implementation of the use of village funds received in stages directly from the APBN has supported village government programs to carry out village development prioritized in the maintenance of community welfare facilities and infrastructure, economic and social education enterprises, and the field of village community empowerment by developing entrepreneurship, as well as expanding individual economics through procurement or capital assistance.